The Libanese Emigration in Western Africa - (:unkn) unknown (My University, 1993)
The migration to South Saharian in Western Africa is one of the old and important components of the contemporary Lebanese emigration. Started in the XIXth Century at the beginning of the 80s and knew a decrease between 1960 and 1970 because of the africanization policies that were followed in some greeting countries but it has been accelerating since 1975 at the beginning of the wars in Lebanon, while the destination countries are changing. Just before the african independences, the number of emigres went up from 40 000 to 75 000 in 1970 and was around 150 000 in the mid 80s. The economical status of the emigres moved, from ordinary wheel of the slave trade to an active element of the diversification of the contemporary economies. This emigration which was at the beginning temporary and once ended the emigres tried to go home in order to settle down, change of nature because of the Lebanese wars. There are more and more « returns » to Europe and to Nothern America. This tendency may increase the problem of the exodus of the Lebanese skills.
Keywords: African Research